The zinc finger/RING domain protein Unkempt regulates cognitive flexibility - Elin Vinsland (Nature Portfolio, 2021)
Abstract Correct orchestration of nervous system development is a profound challenge that involves coordination of complex molecular and cellular processes. Mechanistic target of rapamycin (mTOR) signaling is a key regulator of nervous system development and synaptic function. The mTOR kinase is a hub for sensing inputs including growth factor signaling, nutrients and energy levels. Activation of mTOR signaling causes diseases with severe neurological manifestations, such as tuberous sclerosis complex and focal cortical dysplasia. However, the molecular mechanisms by which mTOR signaling regulates nervous system development and function are poorly understood. Unkempt is a conserved zinc finger/RING domain protein that regulates neurogenesis downstream of mTOR signaling in Drosophila. Unkempt also directly interacts with the mTOR complex I component Raptor. Here we describe the generation and characterisation of mice with a conditional knockout of Unkempt (Unk cKO ) in the nervous system. Loss of Unkempt reduces Raptor protein levels in the embryonic nervous system but does not affect downstream mTORC1 targets. We also show that nervous system development occurs normally in Unk cKO mice. However, we find that Unkempt is expressed in the adult cerebellum and hippocampus and behavioural analyses show that Unk cKO mice have improved memory formation and cognitive flexibility to re-learn. Further understanding of the role of Unkempt in the nervous system will provide novel mechanistic insight into the role of mTOR signaling in learning and memory.